Bone marrow mesenchymal stem cells with low dose bone morphogenetic protein 2 enhances scaffold‐based spinal fusion in a porcine model. (1st November 2021) - Hu, Tao; Liu, Ling; Lam, Raymond Wing Moon; Toh, Soo Yein; Abbah, Sunny Akogwu; Wang, Ming; Ramruttun, Amit Kumarsing; Bhakoo, Kishore; Cool, Simon; Li, Jun; Cho‐Hong Goh, James; Wong, Hee‐Kit
Abstract: High doses bone morphogenetic protein 2 (BMP‐2) have resulted in a series of complications in spinal fusion. We previously established a polyelectrolyte complex (PEC) carrier system that reduces the therapeutic dose of BMP‐2 in both rodent and porcine spinal fusion models. This study aimed to evaluate the safety and efficacy of the combination of bone marrow mesenchymal stem cells (BMSCs) and low dose BMP‐2 delivered by PEC for bone regeneration in a porcine model of anterior lumbar interbody spinal fusion (ALIF) application. Six Yorkshire pigs underwent a tri‐segmental (L2/L3; L3/L4; L4/L5) ALIF in four groups, namely: (a) BMSCs + 25 μg BMP‐2/PEC ( n = 9), (b) 25 μg BMP‐2/PEC ( n = 3), (c) BMSCs ( n = 3), and (d) 50 μg BMP‐2/absorbable collagen sponge ( n = 3). Fusion outcomes were evaluated by radiography, biomechanical testing, and histological analysis after 12 weeks. Mean radiographic scores at 12 weeks were 2.7, 2.0, 1.0, and 1.0 for Groups 1 to 4, respectively. μ‐CT scanning, biomechanical evaluation, and histological analysis demonstrated solid fusion and successful bone regeneration in Group 1. In contrast, Group 2 showed inferior quality and slow rate of fusion, and Groups 3 and 4 failed to fuse any of the interbody spaces. There was no obvious evidence of seroma formation, implant rejection, or any other complications in all groups. The results suggest that the combination of BMSCs and low dose BMP‐2/PEC could further lower down the effective dose of the BMP‐2 and be used as a bone graft substitute in the large animal ALIF model.